The emergence of top‐down, sensory prediction during learning in infancy: A comparison of full‐term and preterm infants. Issue 5 (24th April 2018) - Boldin, Alex M.; Geiger, Romin; Emberson, Lauren L.
Abstract: Prematurity alters developmental trajectories in preterm infants even in the absence of medical complications. Here, we use fNIRS and learning tasks to probe the nature of the developmental differences between preterm and full‐term born infants. Our recent work has found that prematurity disrupts the ability to engage in top‐down sensory prediction after learning. We now examine the neural changes during the learning that precede prediction. In full‐terms, we found modulation of all cortical regions examined during learning (temporal, frontal, and occipital). By contrast, preterm infants had no evidence of neural changes in the occipital lobe selectively. This is striking as the learning task leads to the emergence of visual prediction. Moreover, the shape of individual infants' occipital lobe trajectories (regardless of prematurity) predicts subsequent visual prediction abilities. These results suggest that modulation of sensory cortices during learning is closely related to the emergence of top‐down signals and further indicates that developmental differences in premature infants may be associated with deficits in top‐down processing.